Ўғузномалар: уларнинг сони аслида нечта? - Орипов, Д (FAN va JAMIYAT, 2022)
Oguznoms are one of the most common works among the Turkic peoples. It is noteworthy that the sermons continued from the XII-XIII centuries to the present day.Von Dietz on sermons, H.Kurugli, N.Rakhmonov, F.Bayat, A. Such famous scientists as ticks conducted research. Naturally, there will be more reviews about these works. In this article, a young researcher expresses his opin- ion on new recommendations and justifies them whenever possible.